Beyond emotional intelligence: The new construct of meta-emotional intelligence - D'Amico, Antonella; Geraci, Alessandro (Frontiers in Psychology, 2023)
Meta-emotional intelligence is a recently developed multidimensional construct that, starting from the original ability model of emotional intelligence, focuses on the cognitive aspects of emotional abilities and on the metacognitive and meta-emotional processes that influence our emotional life. Thus, meta-emotional intelligence is the combination of emotional abilities and meta-emotional dimensions, such as the beliefs about emotions, the self-concept about one's emotional abilities, and the self-evaluation of performance. This article aims to illustrate the theoretical and methodological background of this construct and to describe the IE-ACCME test, an original multi-method tool that has been developed to measure the different variables that compose meta-emotional intelligence. Applications of this construct will be discussed, as well as future directions.